A descriptive study: maternal and fetal outcome of grand multipara - Singh, Sunder Pal; Chawan, Jyoti; Mangla, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancies in grand multipara have been considered risky for many decades as there are higher chances of complications during pregnancy, labour and puerperium in these women. This study aims to find out various maternal and fetal complications associated with grand multiparty during pregnancy and labour. Methods: A descriptive observational study was conducted in the department of obstetrics and gynecology of S.K.H.M Medical College Nalhar, Mewat, from Jan, 2014 till Oct, 2014. It included 100 cases of grand multipara women. All the women who delivered at S.K.H.M and had five or more previous viable pregnancies were included in the study. Results: In the total 100 cases that were included in the study, the common medical illness found in grand multipara were anemia (92%), hypertension (13%), preeclampsia (9%) eclampsia (4%) and diabetics mellitus (2%). Other complications observed were mal-presentations (18%), intra-uterine deaths (18%), preterm labor (15%), placental abruption (8%), shoulder dystocia (6%), placenta previa (5%), obstructed labour (4%), and ruptured uterus (2%). Caesarian section was required in 28% of the cases. Third stage complications were also high in grand multi para e.g. PPH (14%), retained placenta (5%), uterine inversion (3%) and maternal mortality (4%). In perinatal outcomes the observations were lbw babies (15%), macrosomies (10%), and APGAR score (8-10) in 70% of the babies. Conclusions: Grand multiparity is still a major obstetric hazard which needs strict supervision and good antenatal care and active intervention at appropriate time. Extreme parity should be treated with extra care especially in populations with high rates of unbooked deliveries.